Phase transition of a microemulsion upon addition of cyclodextrin – applications in drug delivery. (7th February 2018) - Thakur, Sachin S.; Solloway, Jared; Stikkelman, Anneloes; Seyfoddin, Ali; Rupenthal, Ilva D.
Abstract: This study reports on the impact of cyclodextrin addition on the phase behavior of microemulsion systems. Three distinct oil-in-water microemulsions were formulated and subjected to increasing concentrations of various cyclodextrins. The prepared formulations underwent visual, textural and microscopic characterization followed by the evaluation of their in vitro drug release and ex vivo tissue retention behavior. Combining microemulsions with cyclodextrins resulted in either phase separation or transition into a liquid crystalline state depending on the concentration and type of cyclodextrin utilized. Formulations combined with α-cyclodextrin consistently demonstrated transition into a liquid crystalline state as confirmed by polarized light and cryo-scanning electron microscopy. In these cases, cyclodextrin addition was also positively correlated with an increase in formulation hardness, adhesiveness and turbidity. Release and clearance studies revealed that drug diffusion from the microemulsions could be slowed and tissue retention prolonged by increasing the cyclodextrin content. These findings pave the way for the development of novel cyclodextrin-microemulsion-based liquid crystalline formulations in a variety of sustained drug delivery applications.